Development of Digital Teaching Materials for Procedure Texts With Theme of Malay Culinary Typical Based on Book Creators for Sinar Husni Private Senior High School - Ichsan Ardhian, Mhd; Rahmat Kartolo (PT Inovasi Pratama Internasional, 2025)
This research aims to develop a teaching material product, specifically digital teaching materials for procedure texts with the theme of distinctive Malay cuisine, based on Book Creator. It is expected that this product can improve the quality of learning. This research is a development research or research and development that employs the ADDIE development procedure. The product of this research is digital teaching material for procedure texts with the theme of distinctive Malay cuisine based on Book Creator for Class XI of Senior High School. The subjects of this research include material expert validators, media (Design) expert validators, and Indonesian language teachers of Class XI at Sinar Husni Private High School. The research steps consist of analysis, design, development, implementation, and evaluation. The research instruments used in this study include student needs questionnaires, teacher needs questionnaires, material expert validation, media expert validation, pretest and posttest, and responses from the subject teachers. The results of this research indicate that the developed digital teaching materials, using the ADDIE procedure, obtained validation results with a